Hereditary cerebral amyloid angiopathy - Grangeon, Lou (Henry Stewart Talks, 2024)
Cerebral amyloid angiopathy (CAA), Boston Criteria, Alzheimer’s Disease (AD), APP gene and Aβ peptide production, Pathogenic variants, Genotype-phenotype correlation, Down syndrome, CAA and PSEN1, CAA and PSEN2, APOE4 and APOE2 genotype